2003
DOI: 10.1161/01.cir.0000103701.30662.5c
|View full text |Cite
|
Sign up to set email alerts
|

Successful Catheter Ablation of Electrical Storm After Myocardial Infarction

Abstract: Background-We report on 4 patients (aged 57 to 77 years; 3 men) who developed drug-refractory, repetitive ventricular tachyarrhythmias after acute myocardial infarction (MI). All episodes of ventricular arrhythmias were triggered by monomorphic ventricular premature beats (VPBs) with a right bundle-branch block morphology (RBBB

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(180 citation statements)
references
References 25 publications
7
168
2
3
Order By: Relevance
“…In current studies, most of the VPCs originating from Purkinje network were located in the border-zone of MI (5-7).These studies has shown that ablation of these triggers was able to eliminate arrhythmias. Similar results were also demonstrated for patients early after MI (6). However, it is not always easy to find and abolish Purkinje potentials during electrical storm.…”
Section: Discussionsupporting
confidence: 82%
“…In current studies, most of the VPCs originating from Purkinje network were located in the border-zone of MI (5-7).These studies has shown that ablation of these triggers was able to eliminate arrhythmias. Similar results were also demonstrated for patients early after MI (6). However, it is not always easy to find and abolish Purkinje potentials during electrical storm.…”
Section: Discussionsupporting
confidence: 82%
“…26) Furthermore, the arrhythmia substrate of nonischemic cardiomyopathy is more variable and more aggressive ablation strategies targeting all inducible ventricular tachycardia are needed to improve longterm freedom from VAs. [27][28][29] Most of our patients were nonischemic cardiomyopathy, which suggested that RDN could be another choice for VA treatment in this kind of patients. As a simple percutaneous procedure, RDN reduces sympathetic tone and suppress VAs.…”
Section: Discussionmentioning
confidence: 84%
“…A VT-k ezen csoportjánál a ritmuszavar alapja a cikkben felsorolt bármelyik mechanizmus lehet, így az ablatiós stratégia is széles skálán mozog. A sikerarány, különösen ismert vagy valószínűsített trigger felismerése esetén, 24-33 hónapos utánkövetési idő alatt 89-100% közt mozog [38,43]. …”
Section: Polimorf Vt-k éS Vf Ablatiójaunclassified